REVEALING ORBITAL TUMORS: 2-YEAR EVALUATION IN CLINICAL PROFILE, HISTOPATHOLOGICAL FEATURES AND SURGICAL TECHNIQUE - Lisani, Silmi Lisani; Supartoto, Agus; Utomo, Purjanto Tepo; Dibyasakti, Banu Aji; Respatika, Datu (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: Incidence of orbital tumors is relatively low, but the delay in diagnosis, even if benign, can lead to vision loss and deformity. Purposes: This study aims to review clinical and demographic information of orbital tumors in Sardjito General Hospital, Yogyakarta. Method: We retrospectively reviewed clinical data of 138 patients who diagnosed with orbital tumors during July 2021 - March 2023. Data extracted included clinical characteristics, operative procedures, and histopathologic characteristics of orbital tumor. Result: There were 138 orbital tumors managed at hospital during 2-year period. Among 138 patients, 82 patients (59%) were female and 56 patients (40%) were male. Twenty-one patients (15%) were in childhood age and 117 patients (84.8%) were in adulthood age. The common clinical manifestations were proptosis (83.3%) and decreased vision (10.4%). The main procedure used was anterior orbitotomy (54.34%). Eighty-eight patients (63.7%) have primary tumors and 51.4% of the orbital tumors were malignant. The most cases in children were benign tumors (61.9%) meanwhile in adults were malignant (54.7%). The main orbital tumor in childhood age was a Non-Hodgkin Lymphoma (NHL) (19%) and cyst (14.3%). On the other hand, in adult patient, the most common orbital tumor was meningioma (18%) and NHL (15.7%). Conclusion: Orbital tumors are challenging group of tumors with proptosis become the most frequent clinical characteristic that found. The orbital tumors in childhood and adulthood differ significantly in their incidence and tumor type with the percentage of malignant tumors increasing with age.